A Framework of Blue Economics Program Using Blue Sukuk as Socially Responsible and Sustainable Investment - Suryomurti, Wiku; Akbar, Nashr (The International Journal of Business Review (The Jobs Review), 2023)
Abstract. This paper explores the potential issuance of blue sukuk to finance the blue economy project in Indonesia. We first analyze current initiative of Indonesia’s Blue Economics program. Using the theory of change approach, we model the example of blue project and design the suitable sukuk structure to finance the project. We then develop a framework for financing the program using sukuk structures which previously designed for green sukuk.  It is hoped that by issuing the blue sukuk, it may support the SDG program for sustainable finance of blue economics program. Our framework is suitable for both sovereign and corporate blue sukuk. Furthermore, the project-based blue sukuk may support to alleviate the poverty of people who live along the coast and protect them from the impact of climate change. Finally, this study contributes to lay the foundations for further work on Blue sukuk in Indonesia and International as well.Keywords. Blue Sukuk, Blue Economics, Sustainable Finance, Socially Responsible Investment, Climate Change